Openness vs Security: Priorities for the State and Civil Society in the Conditions of Digitalization - N. A. Baranov (Управленческое консультирование)
Digital technologies expand opportunities for human development: life dynamics are increasing, digital platforms are being created for educational, scientific, and political purposes, new opportunities for control over government bodies, and communicative practices are being improved. At the same time, there are new dangers to which a person is exposed. The state and the civilian have both coinciding and differing tasks and priorities. Therefore, there is a need to identify priorities for civil society and the state in the context of technological improvements related to digitalization.